2016
DOI: 10.1007/s40843-016-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Parameter-dependent oxidation of physically sputtered Cu and the related fabrication of Cu-based semiconductor films with metallic resistivity

Abstract: tered Cu atoms. It thus can be imaged that the sufficient oxygen source would lead to a partial or even full oxidation of the growing Cu film. Obviously, such undesirable oxidation would influence the performance, stability and lifetime of Cu film used as interconnection in ULSIC. Moreover, the parameter-dependent oxidation of Cu during physical sputtering deposition has not been investigated systemically yet. Thus, study on the parameter-dependent oxidation of physically sputtered Cu is crucial not only to me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It can be found that the band gap of CuO thin films deposited on polished and unpolished Si wafers is estimated to be 2.03 and 1.94 eV respectively, which are both much larger than that of bulk CuO (1.2 eV). Since the band gap of a semiconductor film is affected by some factors such as quantum size or nanosize effect, doping and defect [15]. In the present case, the nanosize effect including effects of film thickness and building particle and sheet sizes, and the crystal defect in the film may both influence the band gap.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…It can be found that the band gap of CuO thin films deposited on polished and unpolished Si wafers is estimated to be 2.03 and 1.94 eV respectively, which are both much larger than that of bulk CuO (1.2 eV). Since the band gap of a semiconductor film is affected by some factors such as quantum size or nanosize effect, doping and defect [15]. In the present case, the nanosize effect including effects of film thickness and building particle and sheet sizes, and the crystal defect in the film may both influence the band gap.…”
Section: Resultsmentioning
confidence: 86%
“…The other details and parameters can be found in [13]. It has been demonstrated that the residual O 2 in the pre-pumped vacuum chamber is the main oxygen source for the oxidation of sputtering Cu atoms [15]. Relative to the case in [13][14][15], the higher base pressure (2.0×10 −3 versus 5.0×10 −4 Pa) in this work can provide more sufficient O 2 (2.08×10 11 versus 5.2×10 10 atoms/cm 3 , four times) for the oxidation of Cu atoms, which may result in the formation of CuO rather than Cu and Cu 2 O.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the PNFs tend to change the morphology and crystal structure of their building nanostructures thermodynamically. In addition, the valence state of Cu element in Cu2O is +1 (Cu 1+ ), which is also unstable as driven by the tendency of decreasing the free energy [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the last several years, the controllable synthesis of Cu 2 O microand nano-sized crystals with a vast array of architectures, including core-shell Cu 2 O spheres [13], hollow Cu 2 O spheres [14], and porous Cu 2 O spheres [15] has been achieved using electrodeposition method, thermal relaxation method, sonochemical method, vacuum evaporation method, γ-irradiation method, and liquid-phase reduction method [16][17][18]. Additionally, metallic copper (Cu) and copper oxide (CuO) with various structures have also received intense attention, as they can be used in catalysis, sensors, and electronics [19][20][21][22][23][24][25][26]. However, the aforementioned synthesis approaches often involve the use of surfactants, template, and high temperature and pressure to obtain morphology-controllable Cu 2 O structures, which undoubtedly increases the synthesis cost and thus limits their large-scale production.…”
Section: Introductionmentioning
confidence: 99%